The Effect of Purple Leaf Extract (Graptophyllum pictum L. Griff) to The Amount of Fibroblast in Gingiva Rat Wistar induced by Porphyromonas gingivalis - Atik Kurniawati; Savira Aulia Rachim; Pudji Astuti (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2020)
Background: The prevalence of periodontal disease ranks second in dental and oral diseases after caries. Periodontitis is inflammation with bacteria infecting the host and involving all parts of the periodontal tissue. If this condition is left untreated, it can lead to fibrosis and irreversible damage. Various types of periodontitis therapy have not been able to provide optimal results in healing periodontitis and that therapy can cause side effects. Because of this background, the researchers wanted to carry out research on alternative treatments for periodontitis with purple leaves as an anti-inflammatory with an indicator of an increase in the number of fibroblast cells in inflamed areas. The use of purple leaves has been used since ancient times for the treatment of wounds and inflammation. Objective: To determine the effect of purple leaf extract (EDU) on increasing the number of fibroblast cells in the gingiva of Wistar rats infected by Porphyromonas gingivalis (Pg). Methods: 30 Wistar rats were divided into 5 groups, namely the normal group (KN), the control group Pg induced (K +) and the treatment group using EDU 2.5% (P1), EDU5% (P2), EDU10% (P3 ). All groups were induced by Pg except KN. EDU administration once a day for 7 days. On the 7th day the rats were decaputed and their gingivae were taken to make preparations and HE staining was carried out. Results readings in 3 different viewpoints were averaged and analyzed by one-way ANOVA. Results: The results showed that the K + group, 2.5% EDU, 5% EDU and 10% EDU groups increased the number of fibroblast significantly when compared to the Pg group (p < 0.05). Conclusion: EDU can increase the number of fibroblasts in Pg-induced mice